Market power assessment and mitigation in hydrothermal systems. - Kelman, R.
The objective of this work is to investigate market power issues in bid-based hydrothermal scheduling. Initially, market power is simulated with a single stage Nash-Cournot equilibrium model. Market power assessment for multiple stages is then carried through a stochastic dynamic programming scheme. The decision in each stage and state is the equilibrium of a multi-agent game. Thereafter, mitigation measures, especially bilateral contracts, are investigated. Case studies with data taken from the Brazilian system are presented and discussed
Keywords: Brazilian power system; Bid-based hydrothermal scheduling; Bilateral contracts; Game theory; Hydrothermal systems; Market power assessment; Market power mitigation; Multi-agent game; Power generation economics; Single stage Nash-Cournot equilibrium model; Stochastic dynamic programming